Liturgical Music in Rome 1605-45 - Dixon, Graham (Durham Durham University, 1981)
Research has been undertaken on Palestrina, the main figure in Roman liturgical music at the close of the 16th century, and on Carissimi who enjoyed a similar position in the mid-17th century. While there exists a considerable stylistic distinction between the work of these composers, little attempt has been made to trace the transition of the intervening generation. It has been held that Romans so revered the memory of Palestrina as to continue to imitate his style, and to allow no place for the manifestation of an idiom more typical of the seicento, with its monodies and the continuo. The thesis examines this repertory, and indicates that Roman composers did keep pace with progressive tendencies which were becoming apparent throughout the peninsula. The small-scale motet was popular in Rome from the 1590s; the solo and concertato motets gained currency in Rome from the second decade of the century; and the basso continuo was standard from 1603 onwards. A different view therefore emerges from the traditional one stated in Bukofzer's Music in the Baroque Era where Rome is described as the 'bulwark of traditionalism'. Chapter I gives an introduction to previous literature and Chapter II deals with historical and artistic aspects of the period. The thesis then falls broadly into two parts, the one archival and the other dealing with the music. Chapter III discusses references to music in the archives of five churches. The music is then discussed according to liturgical function: the Mass is treated in Chapter IV; music for the divine office (Vespers, Matins and Compline) in Chapter V; and the motet in Chapter VI. Finally, a synthesis of archival and musical material is presented in the one area where this is possible, the multiple-choir repertory commonly called the 'colossal Baroque'.
Printed version of a downloaded doctoral dissertation
Keywords: Palestrina, Giovanni Pierluigi da -- c. 1525-1594; Carissimi, Giacomo -- 1605-1674; 17th Century (1601-1700); Music history; Church music; Musical style; Mass; Motet; Divine office; Rome (Italy)